Orbital granular cell tumor involving the superior rectus muscle: a case report - Wang, Pei; Han, Zijian; Peng, Li; Li, Xiuhong; Yuan, Hongfeng (Frontiers in Oncology, 2024)
ObjectiveThe aim of this case report is to assess the clinicopathological characteristics and differential diagnosis of orbital granular cell tumor (GCT).MethodsClinical and imaging data of a rare case of orbital GCT involving the superior rectus muscle were collected. Its clinical characteristics, imaging, and histopathological features were observed.ResultsA 36-year-old female patient presented with a 2-year history of left eye proptosis. Magnetic resonance imaging (MRI) enhancement suggested a space-occupying lesion in the left superior rectus muscle region. On T1-weighted and T2-weighted MRI, the tumor was isointense to gray matter and significantly enhanced on the enhanced scan. Microscopic examination revealed that most tumor cells exhibited diffuse growth with unclear boundaries, and some cells were arranged in small nests. The tumor cells were large, with abundant, coarse eosinophilic granules in the cytoplasm. Occasional cells contained larger round eosinophilic droplets in the cytoplasm. Focal areas showed foamy cells, small and central round or oval nuclei with occasional nuclear enlargement and mild atypia, inconspicuous nucleoli, rare mitoses, and low proliferative activity. Immunohistochemistry results were Vimentin (+), S-100 (+), CD68 (+), Ki67 (2%+), Inhibin-a (−), CK (−), SMA (−), and Desmin (−). The pathological examination of a specimen harvested from the mass corresponded to a GCT.ConclusionOrbital GCT is rare and should be considered in the differential diagnosis of orbital tumors. It is essential to distinguish it from thyroid-associated ophthalmopathy, inflammatory pseudotumor, and myohemangioma. Definitive diagnosis requires a comprehensive analysis of clinical, histopathological, and immunohistochemical findings. Surgical excision is the primary treatment for orbital GCTs. For patients with incomplete tumor resection, close follow-up is necessary. Proton beam radiation therapy can be considered to prevent recurrence or metastasis if needed.